2014
DOI: 10.1007/s00228-014-1661-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between statin-induced creatine kinase elevation and genetic polymorphisms in SLCO1B1, ABCB1 and ABCG2

Abstract: Genotyping of the SLCO1B1, ABCB1 and ABCG2 genes deserves consideration as a clinical approach to improve statin safety while concomitantly reducing the burden of blood tests for CK measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 44 publications
2
42
1
2
Order By: Relevance
“…future science group ABCG2 gene polymorphisms as risk factors for atorvastatin adverse reactions Preliminary Communication ciation between statin-related CK elevation and ABCG2 poly morphism [16], but they found no significant association between elevated serum CK levels and ABCG2 polymorphism, which is opposite to our findings. However, only one third of their sample comprised patients on atorvastatin (n = 11) while the findings of the Ferrari et al study are the result of mutual effect of atorvastatin, rosuvastatin and simvastatin and therefore could not explain the individual statin contribution.…”
Section: Probability Of Adr (%)contrasting
confidence: 46%
See 3 more Smart Citations
“…future science group ABCG2 gene polymorphisms as risk factors for atorvastatin adverse reactions Preliminary Communication ciation between statin-related CK elevation and ABCG2 poly morphism [16], but they found no significant association between elevated serum CK levels and ABCG2 polymorphism, which is opposite to our findings. However, only one third of their sample comprised patients on atorvastatin (n = 11) while the findings of the Ferrari et al study are the result of mutual effect of atorvastatin, rosuvastatin and simvastatin and therefore could not explain the individual statin contribution.…”
Section: Probability Of Adr (%)contrasting
confidence: 46%
“…Results of the STRENGTH study showed a nonsignificant increase in myotoxicity in SLCO1B1*5 carriers taking atorvastatin [10]. In addition, three small studies and a meta-analysis did not find a statistically significant association between the SLCO1B1 521C variant and myotoxicity in patients using atorvastatin [13,16,61,62]. It must be taken into account that these studies included a rather small number of patients and there is a possibility that they were not able to detect an actual association.…”
Section: Probability Of Adr (%)mentioning
confidence: 83%
See 2 more Smart Citations
“…They found a reduced frequency of the ABCB1 T-non-G-T haplotype (C1236T-G2677T/A-C3435T) in patients having experienced myalgia compared to patients who did not experience myalgia (20% vs. 41%; p=0.03). However, a case-control study reported by Ferrari et al [27] of 66 patients (23 treated with simvastatin) found increased frequencies of the ABCB1 1236T and 3435T alleles in the patients that experienced CK elevations. Both Keskitalo et al [28] and Zhou et al [29] reported no association of ABCB1 C1236T-G2677T/A-C3435T haplotype with the pharmacokinetics of simvastatin lactone, but Keskitalo et al [28] reported increased simvastatin acid exposure with the TTT/TTT diplotype.…”
Section: Methodsmentioning
confidence: 97%